Identification and characterization of Salmonella typhi isolates from Southwest Sumba District, East Nusa Tenggara based on 16S rRNA gene sequences - CHARIS AMARANTINI; LANGKAH SEMBIRING; HARIPURNOMO KUSHADIWIJAYA; WIDYA ASMARA (Society for Indonesian Biodiversity, 2011)
Amarantini C, Sembiring L, Kushadiwijaya H, Asmara W T . It was also found that the isolates which belong to S. typhi species formed several different centers of diversity within the 16S rRNA gene tree. Each clade consisted of the strains from different geographical places in the District. Thus, to conclude the inquiry, there was evident inter-geographical spread of the strains and it tended to spread further into more remote areas in the District.